x2+13x-90=3x-15

Simple and best practice solution for x2+13x-90=3x-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x2+13x-90=3x-15 equation:



x2+13x-90=3x-15
We move all terms to the left:
x2+13x-90-(3x-15)=0
We add all the numbers together, and all the variables
x^2+13x-(3x-15)-90=0
We get rid of parentheses
x^2+13x-3x+15-90=0
We add all the numbers together, and all the variables
x^2+10x-75=0
a = 1; b = 10; c = -75;
Δ = b2-4ac
Δ = 102-4·1·(-75)
Δ = 400
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{400}=20$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(10)-20}{2*1}=\frac{-30}{2} =-15 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(10)+20}{2*1}=\frac{10}{2} =5 $

See similar equations:

| 8.6-5.1c-9.4=0.96+6.3c | | 9s/3=21 | | 4x+27=33-x | | 30/q=-5 | | 18=3x+29 | | 55/9+x=245/9 | | -4y-3y=42 | | 5(2x-4)-88=3(2+2x)–30 | | 6{x+5}=12 | | c/10.065+25=27 | | -3+8u-u=-7+6u | | 1/3x-31/3=-4 | | 9s+3=21 | | -45=-3(2b+5( | | 40=16-6r | | f/4=-4 | | 1/22=x+-2 | | 26x=42+18x. | | -20=7x+2(-3x-7) | | -5(x-4)=10 | | -8-8x/8=56 | | (15x+1)=(19x-24) | | 8x+18=11x+29 | | -5r+14.065=-28 | | 500=100e | | 14x-141=199+4 | | 4.b=-36 | | -4(x-5)+2x=3x-6 | | 1.4b-6.02=1.26-9b | | K(-3)=4x-2 | | 2+18x=19x-4 | | -57/20=x+-2 |

Equations solver categories